2001
DOI: 10.1677/joe.0.1700471
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of interleukin-6 on human granulosa cell steroid secretion

Abstract: Numerous studies have shown that a variety of cytokines are involved in the regulation of ovarian function. Interleukin-6 (IL-6), has been found in follicular fluid. In this report we show by immunocytochemical methods the localization of the extracellular domain of the IL-6-receptor and its associated signal transducer glycoprotein gp 130 on the surface of granulosa cells (GCs). The possibility that IL-6 may also influence the basal and FSH-stimulated production of estradiol (E2) and progesterone (Prog) by GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…In the present study, we investigated the changes in the expression of IL-6 receptors (IL-6Rα, IL-6sR and gp130) in granulosa cells and follicular fluid during atresia. The expressions of IL-6Rα and gp130 in human and rat granulosa cells [33,35] and IL-6sR in human follicular fluid [36] have previously been reported. We detected the expressions of IL-6Rα and gp130 in granulosa cells and IL-6sR in follicular fluid from the porcine ovary.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the present study, we investigated the changes in the expression of IL-6 receptors (IL-6Rα, IL-6sR and gp130) in granulosa cells and follicular fluid during atresia. The expressions of IL-6Rα and gp130 in human and rat granulosa cells [33,35] and IL-6sR in human follicular fluid [36] have previously been reported. We detected the expressions of IL-6Rα and gp130 in granulosa cells and IL-6sR in follicular fluid from the porcine ovary.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, it has been revealed that many cytokines are involved in growth, differentiation, atresia, ovulation and luteinization in the ovary [27][28][29]. Although IL-6 affects the folliculogenesis and steroidgenesis of granulosa cells in the ovary [30][31][32][33], there is no clear information on the roles of IL-6 and its receptors in the regulation of granulosa cell apoptosis. As it has been reported that IL-6 and its receptors play important roles in the survival of various cells [17][18][19][20], we hypothesize that they are involved in follicular selection in the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that inflammatory cytokines play an important regulatory role in ovarian activity [38-40]. In particular, the discovery and application of specific inhibitors and gene knockout animals have more substantiated the previous speculation about the involvement of inflammatory cytokines in follicular development and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated whether or not IL-6 is involved in granulosa cell apoptosis during atresia. It has been reported that IL-6 is produced by granulosa cells in human, rat, and bovine ovaries and that it affects the folliculogenesis and steroidgenesis of granulosa cells [28][29][30][31], but in porcine ovaries, IL-6 is produced by immune cells such as macrophages and T cells, not granulusa cells [32]. In the present study, however, we confirmed that IL-6 mRNA was expressed in granulosa cells of healthy, early atretic, and progressed atretic follicles in porcine ovaries.…”
Section: Discussionmentioning
confidence: 99%